Ketahanan Luntur Warna Pewarna Alami Berbasis Propagul Rhizophora mucronata: Pengaruh Variasi Pencelupan dan Jenis Fiksator - Nabilla, Riska Ayu; Nugroho, Ary Susatyo; Ulfah, Maria (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the effect of variations in the number of dips and types of fixatives, as well as their interaction, on the color fastness of batik fabrics dyed using natural dyes based on Rhizophora mucronata propagules. The study used a quantitative approach with an experimental method and a two-factor factorial design, namely variations in the number of dips (3 times, 6 times, and 9 times) and the type of fixative (alum and iron mordant). The parameter observed was color fastness to washing based on the SNI ISO 105-C06:2010 standard. The data were analyzed using the nonparametric Aligned Rank Transform Analysis of Variance (ART ANOVA) test. The results showed that (1) the variation in the number of dips did not significantly affect the color fastness of batik fabric; (2) the type of fixative used also did not have a significant effect; and (3) there was no interaction between the variation in the number of dips and the type of fixative on color fastness. All treatments produced color fastness values in the fair to good category. These findings indicate that under the conditions and range of treatments used, variations in dyeing or the type of fixative did not significantly affect colorfastness, thus requiring further study with a wider range of treatments to optimize the mangrove-based natural dyeing process.